Antihypertensive effect of piperitenone oxide on spontaneously hypertensive rat by regulating calcium balance and reducing endothelin-1 secretion (Bangladesh Journal of Pharmacology, 2017)
The purpose of this study was to investigate the antihypertensive mecha-nisms of piperitenone oxide in spontaneously hypertensive rat (SHR). Compared to control SHR, piperitenone oxide reduced the systolic blood pressure and serum endothelium-1 (ET-1). The nitric oxide (NO) production and ET-1 secretion were significantly inhibited in the noradrenaline-exposed bovine aortic endothelial cells. Piperitenone oxide showed endothelium-independent but concentration-dependent relaxation of the artery rings. The responsible mechanisms appear to be related to the modulation of ET-1 and NO levels. The vasorelaxant effect of piperitenone oxide is independent of endothelium-derived mediators, which is associated with interfering intracellular calcium homeostasis by blocking Ca2+ influx, as well as intracellular Ca2+ release.Video Clip of Methodology:2 min 58 sec:   Full Screen   Alternate